2022
DOI: 10.2147/vmrr.s347337
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Brucellosis: Epidemiology, Public Health Implications, and Status of Brucellosis in Ethiopia

Abstract: Brucellosis is a globally distributed zoonotic disease that causes serious problems in developing countries such as Ethiopia. Brucella abortus is the primary cause of brucellosis in cattle, and Brucella melitensis and Brucella suis also occasionally cause Brucella infection in cattle. Abortion and the retained fetal membrane are typical signs in females, whereas orchitis and bursitis are the known signs in male cattle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 57 publications
0
27
0
2
Order By: Relevance
“…A number of studies have reported higher odds for seropositivity with increased herd size [ 10 , 33 , 39 , 41 , 42 ]. This could be associated with several factors, such as a higher number of animals tested in larger farms, which increases the probability of detecting at least one seropositive animal and/or the reason that as the number of animals goes up the likelihood of transmission of the disease by contact among them increases as well [ 43 ]. Although this bias could have been eliminated by a proper sampling procedure, given that this was a retrospective study, validity of the sampling procedure could not be ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported higher odds for seropositivity with increased herd size [ 10 , 33 , 39 , 41 , 42 ]. This could be associated with several factors, such as a higher number of animals tested in larger farms, which increases the probability of detecting at least one seropositive animal and/or the reason that as the number of animals goes up the likelihood of transmission of the disease by contact among them increases as well [ 43 ]. Although this bias could have been eliminated by a proper sampling procedure, given that this was a retrospective study, validity of the sampling procedure could not be ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…By all means, international exchanges of livestock products and the migration and traveling of people around the world have affected the epidemiological situation of brucellosis. However, many cases of brucellosis are still reported annually in the world and are considered a health challenge, especially in areas where human brucellosis infections are common [35,37]. Accordingly, researchers are conducting various studies to respond to this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Brucellosis is a zoonotic disease worldwide; it is most prevalent in herders, slaughterhouse workers, and dairy farmers. [17][18][19] Internationally, there are six species of Brucella, with B. melitensis being the most common strain in China, followed by Brucella abortus (B. abortus) and Brucella suis (B. suis); B. melitensis is virulent, and the clinical symptoms of the patients are severe; the virulence of B. abortus is relatively weaker, and the clinical symptoms of the patients are mild. 20 Spondylitis and sacroiliitis are the most common manifestations of brucellosis when it invades the bone and joint, of which spondylitis is the most common manifestation.…”
Section: Discussionmentioning
confidence: 99%